A New Method for Minimizing the Unnecessary Handover in High-Speed Scenario - Hoe Tung Yew; Muhammad Haikal Satria; Rindu Nurma Illahi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
The application of Wireless Local Area Network (WLAN) is limited to indoor or pedestrian walking speed environment because the small WLAN coverage will lead to the growth of unnecessary handover rate in high-speed scenario. The previously proposed traveling distance prediction based handover methods assumed mobile terminal (MT) travels at a constant speed is impractical as most of the MTs may not be traveling at constant speed in real environment. These methods have poor performance in case of acceleration because MT will leave the network earlier than the estimated time. In this paper, a new traveling distance prediction based handover scheme that is aware of MT's speed changes is proposed to overcome the limitation of the existing methods. The proposed scheme is adapted to the MT velocity and acceleration or deceleration rate. The numerical result shows that the performance of the proposed scheme is better than the existing handover methods in high-speed scenario. It keeps the probability of unnecessary handover within the user acceptable level in high-speed scenario.